2022
DOI: 10.3390/metabo12060472
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Flavor Precursors and Liberation Mechanisms of Various Dry-Aging Methods in Cull Beef Loins Using Metabolomics and Microbiome Approaches

Abstract: The objective of this study was to characterize and compare the dry-aging flavor precursors and their liberation mechanisms in beef aged with different methods. Thirteen paired loins were collected at 5 days postmortem, divided into four sections, and randomly assigned into four aging methods (wet-aging (WA), conventional dry-aging (DA), dry-aging in a water-permeable bag (DWA), and UV-light dry-aging (UDA)). All sections were aged for 28 days at 2 °C, 65% RH, and a 0.8 m/s airflow before trimming and sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…. Consistent with the present results,Ribeiro et al (2021) andSetyabrata et al (2022) found Lactobacillales, which are anaerobic bacteria, to be the dominant bacteria on wet-aged beef. The authorsTA B L E 2Note: Mean and standard deviation in log CFU/g beef (wet matter).…”
supporting
confidence: 92%
See 4 more Smart Citations
“…. Consistent with the present results,Ribeiro et al (2021) andSetyabrata et al (2022) found Lactobacillales, which are anaerobic bacteria, to be the dominant bacteria on wet-aged beef. The authorsTA B L E 2Note: Mean and standard deviation in log CFU/g beef (wet matter).…”
supporting
confidence: 92%
“…The WST with much higher microbial counts (>5 log CFU/g) than DST showed high levels of succinic acid and acetic acid, which are products of microbial metabolism (Pothakos et al, 2015). The results of amino acid and nucleotide concentrations over the aging time in the present study suggested an inhibition of protein degradation and energy metabolism due to the drying process of the surface of the DST and an increase in protein degradation and energy metabolism due to the additional factor of the microbiota in wet-aged beef (Muroya et al, 2020;Oh et al, 2019) explained that these bacteria groups belong to the meat spoilage bacteria and can degrade proteins and lipids into products such as organic acids and amino acids (Casaburi et al, 2015;Ribeiro et al, 2021;Setyabrata et al, 2022). A higher rate of protein degradation may have a positive effect on the tenderness of beef, but microbial growth with a count of 5-7 log CFU/cm 2 and higher can lead to negative changes and off-flavors in meat (Feiner, 2006;Hulánková et al, 2018).…”
Section: Microbiota and Metabolome Of Beefmentioning
confidence: 55%
See 3 more Smart Citations